Implementasi dan Pelatihan E-government Berbasis Website untuk Optimalisasi Pelayanan Publik di Nagari Supayang, Kabupaten Tanah Datar - Yuhefizar, Yuhefizar; Syaljumairi, Raemon; Asri, Ervan; Sumema, Sumema; Kurniawan Vadreas, Andrew (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2024)
The development of information technology has encouraged the digitization of government services in an effort to improve efficiency, transparency, and accessibility for the community. However, the implementation of e-government at the village or nagari level still faces various obstacles, such as limited infrastructure, low digital literacy of government officials, and administrative systems that are still manual-based. This community service aims to develop and implement a website-based village information system in Nagari Supayang, Tanah Datar Regency, to support the optimization of public services. The methods used include needs analysis, system design, website development, socialization, and training for village officials and the community. The results of the service showed that the developed system was able to increase service efficiency by up to %, while the level of understanding of the apparatus of the digital system increased by 70 points based on the results of the pre-test and post-test. In addition, the user satisfaction survey indicated that more than 90% of the trainees felt ready to operate the system independently. This implementation proves that digitizing village administration services can improve the effectiveness of village or nagari governance and become a model for other nagari in adopting the concept of e-government in a sustainable manner.